Effect of Microplastics on the Bioavailability of (Semi-)Metals in the Soil Earthworm Eisenia fetida - Xue Xiao; Jia-Ling Li; Wan-Li Rao; Chun-Mei Zhao; Er-Kai He; Ye-Tao Tang; Hua-Yi Chen; Rong-Liang Qiu (Agronomy)
Microplastics have a large surface area and hydrophobic characteristics, which helps them to easily adsorb organic matter and trace metals in soil. This interaction has the potential to alter soil physicochemical properties, affect the bioavailability of metals, and finally influence the toxicity of organisms. In the present study, we exposed Cd or As (Cd/As) to the earthworm Eisenia fetida (Savigny, 1826) in uncontaminated paddy soil, both in the presence and absence of polystyrene (PS) MPs (100~300 μm). The results show that MPs exhibit a significant influence on the physicochemical properties of As-contaminated soil, notably reducing the pH while increasing the electrical conductivity (EC), redox potential (Eh), and dissolved organic carbon (DOC), relative to single As treatment. At a Cd concentration of 40 mg·kg−1, the addition of MPs substantially altered the soil properties, decreasing the pH while increasing the EC and DOC. The effect of MPs on the bioavailable Cd content in soil was associated with Cd concentration. Specifically, MPs significantly increased the content of DGT (diffusion gradient technology)-Cd at a Cd concentration of 60 mg·kg−1. Regarding the bioavailable As content in the soil, MPs led to an increase at a high As concentration (40 mg·kg−1). Moreover, the addition of MPs amplified the uptake rate constants (ku) of DGT-Cd/As at various exposure concentrations, expediting the uptake of Cd/As by earthworms. In addition, compared to Cd treatment, the growth inhibition of earthworms in the As-treatment group was more significant due to microplastics. The results show that MPs in terrestrial environments magnify the negative effects of (semi-)metals, a phenomenon intricately tied to the degree of contamination by (semi-)metals. The interaction between MPs and metals may induce higher ecological risks for organisms.